Suggesting a framework for innovation management in the industry of wellness tourism and spas. - Professor Marios Sotiriadis; Professor Cina Van Zyl; Carmen Poole (African Journal of Hospitality, Tourism and Leisure, 2016)
The issue of developing experience innovations in the field of tourism in general and in the industry of wellness tourism and spas in particular, is of crucial importance in today’s competitive business environment. The analysis of innovations might be approached from two perspectives i.e. demand (consumer experience) or supply (business offering). This article adopts the latter approach without neglecting the former, implying a hybrid approach. The article’s focus is on consumers-driven innovation. Hence, the paper’s main aim is to develop and suggest a framework for innovation management in wellness tourism and spas. To attain this aim, the study takes a strategic management perspective and is based upon an extensive literature review. It is estimated that this study would encourage wellness tourism providers to address new demands by consumers and customize their offering.